REA Model, Its Development and Integration as An Enterprise Ontology Framework - Alexey Nikitkov (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: REA enterprise ontology framework, what is it good for? Motivation - The historical approach to accounting and management information system design was based on conventions expected by the end-users: debits and credits, accounting cycles, general ledger and journals, bank reconciliations, budgeting function, and select management reports. This approach resulted in gross inefficiencies, data-duplication, and inconsistencies, difficulty with system update, modification, porting, and restoration. An alternative system design theory has been in development since 1982, an approach that is easy to understand, formulate, document, and implement; an approach that applies a basic semantic model of structuring all information flow into a widely applicable enterprise ontology framework that facilitates economic activities and strategic planning for the whole enterprise. Yet, until now, this approach is insufficiently known and seldom utilized. Idea - Our purpose is to provide a comprehensive theory guide for anyone desiring to be acquainted with the REA. Data - We review 55 publications comprising dominant Resource-Events-Agents (REA) theory research. Tools - Methodologically, we obtain, classify, define, and discuss the content of major research streams within REA domain. Contribution - The paper's contribution is in structured and comprehensive review enabling a novice to REA reader time-efficient acquaintance with the intricacies and benefits of the ontology, and information system researchers with wide-ranging theory review in this domain. We conclude with a discussion of contentions and challenges surrounding REA theory and its future developmental directions.
Keywords: M4; N8; O3; 650; accounting information systems; resource; event; agent; REA model; ontology; enterprise; information system; strategy planning; economic activities; multi-enterprise collaboration